DINAMIKA KEPERCAYAAN RELASIONAL PADA KONSUMEN BISNIS E-COMMERCE DI INDONESIA - Yulianto, Jony Eko; Renanita, Theda (Jurnal Psikologi, 2019)
Despite the growing number of research on the topic of trust in e-commerce business in the field of psychology, most of these works are overly studied under the approach of personal trust that emphasizes individual-based intrapersonal psychological processes. This kind of approach offers useful insights yet remain to be an open discussion, particularly on its ability to explain social relations-based behaviors among Asian societies. The present study aimed to propose the relational trust approach that is arguably more relevant ontologically to Asian people. By involving nine participants in a Focus Group Discussion and eight participants in a series of semi-structured interview and performing thematic analysis to the empirical materials generated, the results revealed that psychological dynamics of relational trust is consisted of two main thematic clusters. Firstly, relational-trust forming phase, which is consisted of reference-based favorability, relational risk mitigation, and relational exclusivity; and relational-trust establishment phase, which is consisted relational confirmation of satisfactory and negligible mistakes. Theoretical implication and recommendations are discussed.